Recent progress in TiO2-Based photocatalysts for conversion of CO2 to hydrocarbon fuels: A systematic review - Hossen, Md. Arif; Solayman, H. M.; Leong, Kah Hon; Sim, Lan Ching; Yaacof, Nurashikin; Abd Aziz, Azrina; Wu, Lihua; Monir, Minhaj Uddin (Elsevier B.V., 2022)
Photocatalytic conversion of CO2 by using sunlight and TiO2 photocatalysts is a promising approach which produce hydrocarbon fuels to meet the future energy demands with hardly affecting the environment. This systematic review aims to provide rigorous overview of recent progress in TiO2-based CO2 photoreduction to produce hydrocarbon fuels along with future challenges. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was adopted to perform this systematic review. It uses explicit systematic approaches that are chosen to prevent bias, resulting in accurate data collection which helps to draw reliable conclusions. Peer-reviewed articles published in English language between year 2018–2022 were chosen from two main databases, namely Web of Science and Scopus. Depending on the search criteria 62 articles were selected for reviewing critically. Literature suggests that TiO2-based photocatalysts have been increasingly used for reducing CO2 to hydrocarbon fuels. Morphological alterations and surface modification techniques have been widely utilized to improve the photocatalytic performance and minimize limitations of pure TiO2. Despite extensible efforts in this field, the utilization of hydrocarbon fuels still far away from practical applications. There are some challenges need to be addressed like environment friendly low-cost synthesis and modification method development, maximum visible light utilization, design of photoreactor with suitable product selectivity and kinetic model development for CO2 reduction. This study portrays increased clarity regarding the advances and way forwards of crucial topics TiO2-based CO2 photoreduction. Such systematic review is crucial for researchers and academicians for setting future planning.